ASSESSMENT AND MONITORING OF CHANGING LAND USE PATTERN BY USING RS & GIS IN THE STRETCH OF KANTHI COASTAL TRACT OF PURBA MEDINIPUR DISTRICT, WEST BENGAL. - Dr. Pijush Kanti Tripathi; Dr. Subrata Giri (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The present study aims to assess the pattern of Land Use / Land Cover Changes and to expound the impact of land use changes in the stretch of Kanthi coastal area of Purba Medinipur District of West Bengal. Human activities along with the natural coastal geomorphic processes are equally responsible for land use changes in the study area. People are becoming associated with more productive work to earn more, but they are not thinking about sustainable development. In Kanthi coastal tract of Purba Medinipur district, there are four blocks mainly Ramnagar-I, Ramnagar-II, Contai-I and Deshapran mainly involved with various agricultural activities and orchard farming. During the last two decades, the brackish water shrimp culture has rapidly increased in this study area. This practice has gradually destroyed the adjoining paddy fields. The soil becomes very much acidic for the same reason. The Land Use map of different years, namely, 2004, 2007, 2010, 2013, 2016, 2019, obtained from LISS-3 and LANDSAT images and digitized, using Arc GIS-10.1, ERDAS 9.1, and GLOBAL MAPPER 12 software. The principal land use was agriculture in the study area which has been rapidly converted fishing ponds and if the trend of changes continues then the area under study will face crisis of food crops and other socio-environmental problems. At present about 52.89 per cent of land is devoted to agricultural practices under agriculture and cropland has a major impact over the hydrological processes of the area. Therefore, the information obtained from change detection of LU/LC aids in providing optimal solutions for the selection, planning, implementation and monitoring of agriculture practices and other developmental processes to meet the increasing demands of human needs with proper and justified land management.